UV Detection Ion Chromatographic of Thiocyanate and other Inorganic Anions in Urine and Saliva Samples for the Identification of Smokers and Non-smokers - Muhammad Amin (ICETIA, 2016)
A simple and practical UV detection ion chromatography (IC) method has been developed for the identification of smokers and non-smokers by determining the concentration of thiocyanate ion (SCN−), and a number of other inorganic anions, such as S2O32−, C2O42−, I−, IO3−, BrO3−, NO2−, Br− and NO3− in human physiological fluid samples such as urine and saliva. The method performed sodium hydrogen carbonate as the eluent and combining with IC-Anion PWxl PEEK separation column in all determinations. The determination of SCN− and other anions are carried out in ultraviolet detection (lambda, λ=210 nm). Good chromatograms were achieved and all target anions were eluted within 45 min. The detection limits were calculated at S/N=3 were 0.11−1.75 ppm (mg/L). The repeatability values were below 4.82, 4.84, and 4.87% for peak height, peak area and retention time, respectively. The developed method was successfully applied to the determination of all targeted anions especially thiocyanate ion (SCN−) in smokers and non-smokers urine and saliva samples. The samples were obtained from healthy adult smoker and non-smoker volunteers